PENGARUH PROFITABILITAS,LEVERAGE DAN UKURAN PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODE TAHUN 2015-2018 - Devi Dean Wardhany; Sri Hermuningsih; Gendro Wiyono (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The purpose of this study was to determine the effect of profitability (ROA,ROE), leverage (DER), and FIRM SIZE) and then effect on firm value (PBV) of the company’s value on the LQ45 in Indonesia Stock Exchange. The population in this study are all company LQ45 in the Indonesia Stock Exchange amounted to 45 companies in the period 2015-2018. Sampling technique used was purposive sampling, so that the final sampel obtained was 26 companies belonging to the LQ45 in the Indonesia Stock Exchange. Source of data in this research is secondary data obtained from www.idx.co.id. Based on the results of the analysis that the profitability has two proxy namely ROA has a significant effect in firm value and the profitability ROE has significant effect in firm value, leverage is has proxy DER a significant effect in firm value, and firm size is positive but not significant on firm value.